IMPLEMENTASI PERAN BABINSA DALAM PEMBINAAN KESADARAN BELA NEGARA(Studi Kasus pada Koramil 03 Kecamatan Mojosongo Kabupaten Boyolali) - SARI, ATIKA PURNAMA; , Drs. Achmad Muthali'in,M.Si (2016)
ABSTRACT Atika Purnama Sari/A220120047. IMPLEMENTASI PERAN BABINSA DALAM PEMBINAAN KESADARAN BELA NEGARA (Studi Kasus pada Koramil 03 Kecamatan Mojosongo Kabupaten Boyolali). kripsi. Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Surakarta. Juni, 2016. This study aims to describe the implementation of Babinsa role in fostering awareness to defend the country in the territory of the District Koramil 03 Mojosongo Boyolali include implementation, obstacles encountered, and the solutions provided. This study used a qualitative research with case study strategy. Data collected by observation, interview and documentation. Test the validity of the data by triangulation of data sources and data collection techniques. Analysis of the data using interactive analysis techniques through data collection, data reduction, resentation and conclusion. The results showed that the clerk to provide awareness training to defend the country in the community especially the youth is Babinsa. Babinsa cooperate with the village head and the village committee to provide guidance and supervision of awareness to defend the country, extension of rural development in the field of state defense, control or infrastructure facilities in rural or village defense, and reports on social conditions in the countryside or village. Obstacles encountered when implementing guidance or supervision of which is the number of activities carried out by Danramil and Babinsa, the bustle of people in work, and a sense of community wareness is still low. The solution that has been done is approach or socialization on young girl or boy to make a deal every month or week held a meeting to give awareness to defend the country and further enhanced sense of concern for the development of rural communities in the field of defense and security through the socialization of the village chief or other village officials who cooperate with Babinsa. Keywords: implementation, training, civil defense, Babinsa